2018
DOI: 10.9770/jssi.2018.7.3(14)
|View full text |Cite
|
Sign up to set email alerts
|

Savings and Credit Cooperatives in Pichincha, Ecuador: Is This a Sustainable Social Management Case?

Abstract: Cooperatives have the potential to develop an economic, social and environmental activity in a sustainable manner. In particular, social management is aimed at meeting the needs of its partners, families and community in an efficient and effective way. A study of social management was carried out in 60 savings and credit cooperatives in Pichincha, Ecuador, to determine if this is carried out under sustainability principles, with the determination that the recognition of social responsibility and the integral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…The specific area of this research is focused on the cooperativism of Ecuador, whose management and study has traditionally been directed towards economic, financial or production matters without considering the activities intended to improve the life quality of stakeholders in a sustainable way [23,25]. Due to this, the preparation of tools which allow the measurement of this construct is key, and, additionally, these tools must meet the specific characteristics of the context where they are going to be applied [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific area of this research is focused on the cooperativism of Ecuador, whose management and study has traditionally been directed towards economic, financial or production matters without considering the activities intended to improve the life quality of stakeholders in a sustainable way [23,25]. Due to this, the preparation of tools which allow the measurement of this construct is key, and, additionally, these tools must meet the specific characteristics of the context where they are going to be applied [39].…”
Section: Discussionmentioning
confidence: 99%
“…As we have seen before, this research considers the analysis of corporate sustainability in Ecuadorian corporations due to the growing need to investigate the said practices in the area of a solidary and popular economy [23]. The denomination of "solidary and popular economy" is commonly used in Latin American countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With reference to this, Papasolomou and Vrontis (2006) consider that investing in employee motivation is undoubtedly an essential requirement in the search for competitive advantages in businesses. As such, the essence of co-operatives, as social economy businesses, is related to the internal marketing dimensions given that it is based on balance among material, financial, and human resources (Fernández et al, 2018). Similarly, Ahmed and Rafiq (2003) indicated that internal marketing helps the development and maintenance of the inter-functional relationships among employees who, as internal customers, are involved in the co-creation of value, which is used to attain success within the organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The question of what moves markets have been debated for ages (Mentel et al, 2016;Zemlickiene et al 2017;Michailova et al, 2017;Masood et al, 2017;Peker et al 2017;Ahmed et al 2018;Abbas, 2018;Jankelová et al, 2018;Fernández et al, 2018;Veselovsky et al, 2018). The main issue is that the movement in the markets is a result of the pricing of information, the efficient market hypothesis advocated by Malkiel (1962) and Fama (1965), or the reaction of the market participants to the information, behavioural finance theory advocated by Statman (2008) and Subrahmanyam (2007) amongst others.…”
Section: Introductionmentioning
confidence: 99%